OCURRENCIA ESTACIONAL DE LAS PRINCIPALES ESPECIES DE COCCINELLIDAE DEPREDADORAS DE Taxoptera citricida EM CITRICOS - Guerreiro, Julio CÃ©sar; Berti Filho, Evoneo; Busoli, Antonio Carlos; Ruiz, Marcelo Gustavo (REVISTA DE AGRICULTURA, 2015)
OCURRENCIA ESTACIONAL DE LAS PRINCIPALES ESPECIES DE COCCINELLIDAE DEPREDADORAS DE Taxoptera citricida EM CITRICOS